How do germ cells choose their sex? Drosophila as a paradigm. - Steinmann-Zwicky, M. (BioEssays, 1992)
Sex determination in the germ line may either rely on cell-autonomous genetic information, or it may be imposed during development by inductive somatic signals. In Drosophila, both mechanisms contribute to ensure that germ cells are oogenic when differentiating in females and spermatogenic when differentiating in males. Some of the genes that are involved in germ line sex determination have been identified. In other species, including vertebrates, inductive signals are commonly used to determine the sex of germ cells.